Fundamental of Entrepreneurship ENT300 : CTC Cafe / Mohamad Afiq Jemat Mohd Hafiz Jemat... [et al.] - Mohd Hafiz Jemat, Mohamad Afiq Jemat; Clement, Nicholas Ngau; Hussain, Mohammad Fikri; John Panggau, Jeremiah Kana; Rechie, Russell Mambak (2020)
CTC Café is a fast food restaurant located in Desa Ilmu, Kota Samarahan. The café was first opened in February 2016. CTC Café is a fast food restaurant that sells various types of local dishes and also beverages. CTC Café is very famous for its’ Mee Kolok. CTC Café is owned by a local business man named Mohammad Firdaus. This café is handled by Mr. Firdaus himself and also from the help the staffs of CTC Café. The CTC Café’s owner and staffs are currently working on achieving their business goal which is to be one of the most successful café in Kota Samarahan. They also hope that they can open more branches in the future. This café’s targeted customers are the locals, office men and women from the industrial places nearby and also the students from the universities nearby. These customers are the main contributors for the café development. In conclusion, CTC Café is a fast food restaurant that is located in Desa Ilmu, Kota Samarahan and this café attract plenty of people that live in Desa Ilmu.